The determinants that influence the growth of tourism sector in Melaka / Nursyafawati Shawal (Faculty of Business and Management, 2008)
Tourism is one industry that quickly develops in our country, Malaysia. It is because the tourism industry is one of the major contributors to the National Income. This research is conducted to assess the factors that influence the increasing number of tourists' arrival in Melaka. The State Government does many things to promote Melaka as the one of the state that the tourists should visit when they visit Malaysia. Melaka use the tag line of 'Visit Melaka means visit Malaysia'. In this research, researcher found that there are positive relationship between the exchange rate and the gross domestic product to the growth of tourism industry. However, the inflation rate has a negative effect on the growth of tourism sector. The objectives of the research are to determine the growth of tourism sector in Melaka, to identify the important factors that influence tourism sector in Melaka and to explore ways how to increase the number of tourists in the future.